PENERAPAN EVIDENCE BASED NURSING: EFEKTIVITAS SUPERVISI REFLEKTIF INTERAKTIF UNTUK MENINGKATKAN MOTIVASI PERAWAT DALAM MELAKSANAKAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI IGD RS BHAYANGKARA TK. I RADEN SAID SUKANTO - Gilang Dermawan (2023)
Supervision is a management function at the control stage which is carried out to direct nurses to work effectively, efficiently, and reduce potential work problems. Motivation is a human psychological characteristic that contributes to a person's level of commitment. One of the supervision models carried out in hospitals to increase nurse motivation is an interactive reflective supervision model. The purpose of this study was to determine the effect of interactive reflection supervision on the motivation of nurses to document nursing care in the IGD of Bhayangkara Hospital TK.1 Raden Said Sukanto. The research design used in this study was a quasi-experimental pre and post test, with a sample of 25 nurses in the intervention group. The research instrument used a questionnaire calculated on a Likert scale with a maximum value of 4 and a minimum of 1. The analysis used dependent T and Wilcoxon Signed Ranks. The results showed that there was a significant difference between the motivation of nurses in documenting nursing care before intervention and after intervention. The conclusion is that there is an effect of interactive reflective supervision on the motivation of nurses in carrying out nursing care documentation. This study recommends that interactive reflective supervision can be applied in hospitals as a way to increase nurse motivation in documenting nursing care.